2016
DOI: 10.1039/c6nj00924g
|View full text |Cite
|
Sign up to set email alerts
|

DFT investigation of Ni-doped graphene: catalytic ability to CO oxidation

Abstract: Theoretical investigations predict that Ni-doped graphene is a promising catalyst for CO oxidation at mild temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…Moreover, although the entire reaction through the ER mechanism is exothermic, however, this endothermic reaction step along with the large energy barrier for the formation of CO 3 intermediate indicate that the CO oxidation through the ER mechanism is almost impossible over CuN 3 ‐Gr. This finding is in agreement with other related studies …”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Moreover, although the entire reaction through the ER mechanism is exothermic, however, this endothermic reaction step along with the large energy barrier for the formation of CO 3 intermediate indicate that the CO oxidation through the ER mechanism is almost impossible over CuN 3 ‐Gr. This finding is in agreement with other related studies …”
Section: Resultssupporting
confidence: 94%
“…Unlike O 2 molecule, our results indicate that CO adopts an end‐on configuration over CuN 3 ‐Gr, in good agreement with other reports . In the optimized configuration, CO molecule is attached to the Cu atom via its carbon site.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In particular, most of these metal‐doped graphene sheets have been studies for the CO oxidation . For instance, quantum chemical calculations have indicated that the chemical doping of graphene with atoms like Si, Al,, Ni, Fe or metal clusters provide quite low reaction energies comparable with those of noble metal catalysts. Among those, transition metal (TM) doped graphene sheets are considered as a low cost catalyst that can proceed the reaction under a mild condition ,,,,…”
Section: Introductionmentioning
confidence: 99%